2013
DOI: 10.1080/02699931.2013.865595
|View full text |Cite
|
Sign up to set email alerts
|

Robust anger: Recognition of deteriorated dynamic bodily emotion expressions

Abstract: In two studies, the robustness of anger recognition of bodily expressions is tested. In the first study, video recordings of an actor expressing four distinct emotions (anger, despair, fear, and joy) were structurally manipulated as to image impairment and body segmentation. The results show that anger recognition is more robust than other emotions to image impairment and to body segmentation. Moreover, the study showed that arms expressing anger were more robustly recognised than arms expressing other emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
(27 reference statements)
3
14
0
Order By: Relevance
“…These results are also in good accordance with recent work showing that angry body postures are detected more rapidly than happy body postures in an analogue of the face-in-a-crowd effect (Gilbert, Martin, & Coulson, 2011). Our findings also complement the research by Visch et al (2014) who found that recognition of anger from bodily expressions is highly robust with respect to stimulus degradation and more robust than recognition of fear, despair and joy.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are also in good accordance with recent work showing that angry body postures are detected more rapidly than happy body postures in an analogue of the face-in-a-crowd effect (Gilbert, Martin, & Coulson, 2011). Our findings also complement the research by Visch et al (2014) who found that recognition of anger from bodily expressions is highly robust with respect to stimulus degradation and more robust than recognition of fear, despair and joy.…”
Section: Discussionsupporting
confidence: 94%
“…Interestingly, in the latter study, facial expressions of anger were not well detected from a distance despite the obvious advantage of detecting threat from a distance. However, natural viewing conditions include a body which may better convey anger distally due to its larger size and broad dynamic patterns (Dael et al, 2012(Dael et al, , 2013 Recent work using dynamic expressions compared the recognisability of face and body cues across different emotions and increasing degrees of deteriorated viewing conditions (Visch, Goudbeek, & Mortillaro, 2014). Specifically, participants viewed emotional displays from intact videos, silhouettes with details, broad forms with no details or light point coordinates.…”
mentioning
confidence: 99%
“…In contrast, a fearful expression was marked by forearm activity, followed by an equally strong involvement of shoulders and biceps, while activity of the triceps is quite low (see Figure 5). Considering the function of the muscles, these findings are in line with previous descriptions of angry and fearful movements, such as raising the forearms to the trunk or stretching the arms downward with palms held up (anger) and lifting the arms with the hands held up protectively with the palms outward (fear) (De Meijer, 1989; Wallbott, 1998; Sawada et al, 2003; Coulson, 2004; Kleinsmith et al, 2006; Kessous et al, 2010; Dael et al, 2012b). See Figure 1 for examples of these movements in the stimuli.…”
Section: Discussionsupporting
confidence: 90%
“…Several previous works support the importance of anger expressed via body motion: Pichon and colleagues have shown that a response to anger expression results in even more activation of defense mechanisms (“fight or flight”) than a response to fear expressions when the perceiver is the target of the anger (Pichon et al, 2009). A similar tendency is discussed in a recent study by Visch et al (2014), where recognition of anger expressed in the body motion was the most robust under various stimuli degradation conditions (including a condition where only parts of the upper body were portrayed). Others have found that a bias toward anger is even more pronounced in violent offenders (Kret and Gelder, 2013).…”
Section: Discussionsupporting
confidence: 83%